The modeling of earthquake disaster mitigation in Bulukumba Regency: A stakeholder approach - Ahmad, Despry Nur Annisa; Tarigan, Suria Darma; Tjahjono, Boedi; Sitanggang, Imas Sukaesih; Sakti, Harry Hardian (Brawijaya University, 2025)
Bulukumba Regency, located along the Walanae Fault and within a seismic gap zone, indicates the potential for future earthquake recurrence. However, the regional and community capacity to address earthquake hazards remains weak, as evidenced by the lack of regulations accommodating earthquake studies in Bulukumba. This study aimed to design an earthquake mitigation model based on a stakeholder approach in Bulukumba Regency. The methodology employed MACTOR (Matrix of Alternatives for Choice and Trade-Offs), utilizing survey and questionnaire data. The output is a framework for policymakers in earthquake mitigation activities. The results suggested two effective alternative models: (i) a stakeholder formulation model based on role capacity and (ii) a time segmentation model for stakeholder involvement in earthquake mitigation. Based on these two models, it is essential to establish strong coordination and collaboration among these actors in order to minimize the impact of disasters on both the community and the environment.